Analysis of fractional duffing oscillator - Eze, S.C. (Revista Mexicana de Física, 2020)
In this contribution, a simple analytical method (which is an elegant combination of a well known methods; perturbation method and Laplace method) for solving non-linear and non-homogeneous fractional diﬀerential equations is pro- posed. In particular, the proposed method was used to analysed the fractional Duﬃng oscillator.The technique employed in this method can be used to analyse other nonlinear fractional diﬀerential equations, and can also be extended to non- linear partial fractional diﬀerential equations.The performance of this method is reliable, eﬀective and gives more general solution.